Kajian Tingkat Penerapan Manajemen Mutu Terhadap Kinerja UMKM Sektor Agro-Industri Pangan Olahan Nata de Coco di Kota Bogor - Linda Elfrida Pandjaitan; Muhammad Syamsun; Darwin Kadarisman (Institut Pertanian Bogor, 2011)
Study of quality management implementation in Small Medium Enterprises (SMEs) nata de coco industry in the city of Bogor. The purpose of this study are: (1) to see what extent the application of quality management in the SME sector, Agro-food industry processed commodities nata de coco in the City of Bogor, (2) the relationship between the level of implementation of quality management on the performance of SMEs Agro-industrial sector Prepared Food commodities nata de coco in the City of Bogor. Analysis of the application of quality management level with the company's performance against the trend ratio analysis of financial performance and trend of non-financial performance. The trend of financial performance ratios in the analysis of: (a) the ratio of net income, (b) the ratio Net Present Margin (NPM), (c) the ratio of profits to capital (Return on Equity or ROE). Trend analysis performed on non-financial performance: (a) the type of production, (b) the volume of production, (c) the number of customer. The aspects quality control of quality management activities on nata de coco industry has not fully implemented. Improved financial performance in industries that had reached stage Quality Control System (QCS): (a) the trend of the ratio of net income increased to the MMI 5%, (b) trend ratio of NPM rising increased against Mitra Makmur Industri (MMI) 4%, and (c) trend ratio of ROE increased against MMI 2%. Non-financial performance improved in the industry that had reached stage QCS: (a) trend of type of production increased against AFG 58%, (b) trends in production volume increased against AFG 75%, and (c) the trend of the number of customer increased against AFG 105%. Relations with the level of implementation of quality management of financial performance will go toward growth when the industry is consistent in applying quality management so that the market receiving the product and the profits from the increasingly large. Application of quality management level contact with non-financial performance has increased consistently in the application so that when the market receives products that increase the production volume.